The Brussels International Declaration on Lipoprotein(a) Testing and Management - Kronenberg, Florian; Bedlington, Nicola; Ademi, Zanfina; Geantă, Marius; Silberzahn, Tobias; Rijken, Marc; Kaal, Aedan; Harada-Shiba, Mariko; Chen, Zhenyue; Thanassoulis, George; Eliasen, Bogi; Eiselé, Jean-Luc; et al. (Atherosclerosis, 2025)
There is striking evidence that a high lipoprotein(a) [Lp(a)] concentration is a strong, independent, and causal cardiovascular risk factor. However, Lp(a) testing rates are very low (1 %-2 %) despite the fact that 1 in 5 individuals have elevated Lp(a) concentrations. The Brussels International Declaration on Lp(a) Testing and Management was co-created by the Lp(a) International Task Force and global leaders at the Lp(a) Global Summit, held in Brussels, Belgium, on March 24-25, 2025. The event, organized by FH Europe Foundation, brought together scientific experts, people with the lived experience of elevated Lp(a) and policy makers from the European Institutions and World Health Organization. The World Heart Federation, Global Heart Hub, and European Alliance for Cardiovascular Health and scientific organizations such as European Atherosclerosis Society, and International Atherosclerosis Society were formal partners. The Summit was hosted by a Member of the European Parliament, Romana Jerković, and held under the patronage of the Polish presidency of the Council of the European Union. The Declaration calls for 1) integration of Lp(a) testing and management into Global, European and National Cardiovascular Health Plans; 2) appropriate investment, policy and programmes in targeting Lp(a) testing and management based on a recent study demonstrating the substantial overall cost-saving to health systems across the globe; 3) political commitment to mandate systematic Lp(a) testing at least once during a person's lifetime, ideally at an early age, with full reimbursement; 4) incorporation of Lp(a) test results in the context of a person's cardiovascular risk assessment, with development of personalised cardiovascular health roadmaps as needed, without fear of dredit aiscrimination; 5) investment in public and healthcare professional education to increase awareness of Lp(a) and its impact on cardiovascular health.
Keywords: kardiovaskulární nemoci; Consensus; Cardiovascular risk evaluation; lidé; hodnocení rizik; Cardiovascular risk; Patient engagement; Lipoprotein(a); Screening; biologické markery; Cardiovascular Diseases; lipoprotein (a); konsensus; Biomarkers; Risk Assessment; Humans